Sua maestà anatomica il potente e oscuro splendore della malattia = His anatomical majesty : the potent and obscure splendour of disease - Vannini, Carlo 1956- (Logos edizioni, 2016)
"In this book, the reader is literally taken by hand and accompanied to observe the wonders of the Morgagni Pathological Anatomy Museum which, besides collecting documents and writings by Giovanni Battista Morgagni, houses over 1500 preparations, dry, alcoholic or formalin, tannins; these finds not only document the most terrible morbidities and dysfunctions, but also open up a window of what it meant to be ill two or three hundred years ago. Places ahead of the incredible architecture of the anatomical machine , we can not help but be admired as children in the face of strange marching. The pathological body, which is shown in detail in these pages with a subtlety of detail, is a free body, forgetting of every limit, in which the passage of the illness leaves the carved carved and unpredictably marked until it becomes a meeting of science and art. That's why the Morgagni Museum is a rich place not only for history and medicine, but also for the most fertile kind of enchantment, which leaves interdicted and disturbed." -- Publisher's description
Text in italienischer und englischer Sprache
Keywords: Morgagni, Giambattista / 1682-1771; Università di Padova / Museo di anatomia patologica; Anatomy, Artistic; Pathology; Exhibits as Topic; Photography; Italy; Catalog; Bildband